Automatic refactoring of legacy Fortran code to the array slicing notation - Rajaseharan, Chandrasehar (2013)
There are many legacy Fortran programs still in use today, especially scientific codes which were written decades ago. Many of these codes use explicit DO-loops in programs that tend to clutter the code and make it harder to understand and maintain. Modern features of the Fortran language, such as the array slicing notation and introduction of commonly used intrinsic functions, go a long way in helping programmers write code that is easier to read and maintain. We introduce a refactoring tool that can help to transform code to make use of the array slicing notation and related intrinsic functions.